Augmentation of Demineralized Bone Matrix Post-Tooth Extraction Increases The Density of Gingival Collagen Fiber of Rabbit Mandible - Regina TC Tandelilin (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2010)
Most cases report that the abnormality of bone defect is engendered by tooth extraction. The powder of demineralized bone matrix (DBM) is required to fill alveolus bone for reconstructing material or preventingtissues defect after tooth extraction. The aim of this study was to determine the density of gingival collagen fiber on wound healing after the augmentation of DBM following the extraction of incisivus tooth. In this study, 36 male rabbits aged 2.5-3 months weighing 900-1,100 grams were randomly divided into two groups: control and treated rabbits. The incisivus teeth of mandibles of treated rabbits were extracted and augmented with the allograft DBM powder. The gingival was sutured with non-absorbable sutures. The same procedures were employed to the control group, except that these rabbits were augmented with DBM powder. Subsequently, the rabbits were sacrificed on days 1, 3, 5, 7, 10, and 14 after surgery, and each observation was represented by three rabbits in the sample. The gingival (ca. 0.5-1cm) was cut and fixed immediately in 10% paraformaldehide. The staining was done using van Geison. In the treated rabbits, the density of gingival collagen fiber significantly increases in all observation days except on first day, indicating that the allograft powder of DBM successfully accelerates the wound healing process.